Zarządzanie wiedzą a kształtowanie kultury organizacyjnej przedsiębiorstwa wielonarodowego - Piwowar, Katarzyna (Knowledge management in the context of building organizational culture in multicultural enterprise, 2006)
In context of building organizational culture in a multicultural enterprise cultural differences have a special meaning. The paper is aimed at the presentation of utility of knowledge management concept in creating corporate culture of “overcoming differences”. Knowledge about the differences and employees’ opinion about the prevailing organizational culture should be the basis of creating direction of changes. The results of the author’s empirical research present the shortage of training in cultural differences and studies of employees’ opinion in five multicultural companies of high technology situated in Lower Silesia.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 399-407